Slot Time Policy and Dual-Use Coordination: Managing Training Flight Operations at Banyuwangi Airport - Mubarok, Ahmad; Wardana, Miko Andi; Prasetyo, Kukuh Tri (SAFE-Network, 2025)
Regional airports increasingly face operational challenges as they accommodate both commercial aviation and pilot training activities within limited infrastructure and airspace. Banyuwangi Airport in East Java, Indonesia, represents a dual-use facility that has adopted a time-based slot allocation system to manage growing traffic from airlines and aviation academies. This study analyzes the structure and effectiveness of the airport’s slot time policy using a qualitative-descriptive approach based entirely on secondary data, including policy documents, operational manuals, and scholarly literature. The findings show that while the policy provides functional time segmentation-allocating daytime hours for commercial operations and nighttime for training-it lacks formal regulatory support and is executed through manual, informal coordination. These limitations are compounded by infrastructural constraints such as a single runway, limited apron capacity, and the absence of digital scheduling tools. Additionally, relegating flight training to nighttime hours compromises the quality of visual flight instruction. The study concludes that although the existing policy reduces immediate operational conflict, it is not sustainable in its current form. Strengthening the policy through regulatory formalization, infrastructure enhancement, and digital slot coordination platforms is essential for ensuring both operational efficiency and the long-term viability of Indonesia’s aviation training sector.